Perovskite Photodetectors Based on p-i-n Junction With Epitaxial Electron-Blocking Layers - Xu, Yubing; Wang, Xin; Pan, Yuzhu; Li, Yuwei; Emeka Elemike, Elias; Li, Qing; Zhang, Xiaobing; Chen, Jing; Zhao, Zhiwei; Lei, Wei (Frontiers in Chemistry, 2020)
Organic-inorganic hybrid perovskite single crystals (PSCs) have been emerged as remarkable materials for some optoelectronic applications such as solid-state photodetectors, solar cells and light emitting diodes due to their excellent optoelectronic properties. To decrease the dark current, function layers based on spin-coating method are frequently requested for intrinsic PSCs to block the injected current by forming energy barrier. However, the amorphous function layers suffer from small carrier mobility and high traps density, which limit the speed of the photoelectric response of perovskite devices. This work supposes to grow MAPbBr3 and MAPbI3 mono-crystalline thin films on the surface of intrinsic MAPbBr2.5Cl0.5 PSCs substrate by a heteroepitaxial growth technique to act as electron-blocking layers. Meanwhile, C60 and [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) layers are deposited on the opposite surface of substrate PSCs by spin-coating method to block injected holes. This Au-MAPbI3-MAPbBr3-MAPbBr2.5Cl0.5PSCs-C60-PCBM-Ag heterostructure can be used as excellent photodetectors due to its low dark current density of 6.97×10-11 A cm-2 at -0.5 V bias, high responsivity of 870 mA/W at -100 V bias and X-ray sensitivity as high as 59.7 µC mGy-1 cm-2 at -50 V bias.